Effect of the aspartic acid D2 on the affinity of Polybia-MP1 to anionic lipid vesicles - Leite, Natalia Bueno [UNESP]; Alvares, Dayane dos Santos [UNESP]; Souza, Bibiana Monson de [UNESP]; Palma, Mario Sergio [UNESP]; Ruggiero Neto, Joao [UNESP] (Springer, 2014)
Polybia-MP1 (IDWKKLLDAAKQIL-NH2), a helical peptide extracted from the venom of a Brazilian wasp, has broad-spectrum antimicrobial activities without being hemolytic or cytotoxic. This peptide has also displayed anticancer activity against cancer cell cultures. Despite its high selectivity, MP1 has an unusual low net charge (Q = +2). The aspartic residue (D2) in the N-terminal region plays an important role in its affinity and selectivity; its substitution by asparagine (D2N mutant) led to a less selective peptide. Aiming to explore the importance of this residue for the peptides' affinity, we compared the zwitterionic and anionic vesicle adsorption activity of Polybia-MP1 versus its D2N mutant and also mastoparan X (MPX). The adsorption, electrostatic, and conformational free energies were assessed by circular dichroism (CD) and fluorescence titrations using large unilamellar vesicles (LUVs) at the same conditions in association with measurement of the zeta potential of LUVs in the presence of the peptides. The adsorption free energies of the peptides, determined from the partition coefficients, indicated higher affinity of MP1 to anionic vesicles compared with the D2N mutant and MPX. The electrostatic and conformational free energies of MP1 in anionic vesicles are less favorable than those found for the D2N mutant and MPX. Therefore, the highest affinity of MP1 to anionic vesicles is likely due to other energetic contributions. The presence of D2 in MP1 makes these energetic components 1.2 and 1.5 kcal/mol more favorable compared with the D2N mutant and MPX, respectively.
Keywords: Antimicrobial peptide; Peptide-membrane interaction; Electrostatic and nonelectrostatic free energy